Stydy of the spectrum of scintillation aplitude generated by fast neutron in an organic scintillator - Martynenko, E.V. (Functional Materials, 2007)
The features of the organic scintillator light yield as a function of the ionizing radiation energy at high specific energy losses (dE/dx) taking fast neutrons as an example have been considered. The dependences of light yield on the neutron energy have been obtained in experiment for stilbene single crystal and the liquid scintillator (diisopropyl naphthalene + BPO, 5 g/l) under irradiation by ²³⁹Pu—Be neutron source. A method of neutron spectra reconstruction basing on recoil proton spectra has been described and the obtained spectra for ²³⁹Pu-Be source have been presented.